Exploring Reading Comprehension Profiles of First-Year Pre-Service Elementary Teachers: A Descriptive Survey Analysis Based on Barrett’s Taxonomy - Neneng Sri Wulan; Indah Nurmahanani; Nadia Tiara Antik Sari; Nenden Permas Hikmatunisa; Tiara Yogiarni; Tazqiyah Rimba Mazid Nugraha (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2026)
Reading comprehension is a critical yet frequently underexamined competency among pre-service elementary teachers, whose future role requires them to model and scaffold literacy development for young learners. Despite its importance, comprehensive profiling of reading comprehension across all levels of Barrett’s Taxonomy among first-year students in Indonesian teacher education programs remains limited. This study aimed to analyse the reading comprehension profiles of 158 first-semester students in the Elementary School Teacher Education (PGSD) program using a descriptive survey design. Data were collected through a validated reading comprehension test grounded in Barrett’s Taxonomy, comprising five indicators: literal, reorganisation, inferential, evaluation, and appreciation, supplemented by semi-structured interviews with 12 purposively selected students. Descriptive statistical analysis revealed a mean score of 68.58 with a standard deviation of 20.92, placing overall performance in the moderate category. A coefficient of variation of 30.5 per cent indicated considerable within-cohort heterogeneity. Indicator-level analysis showed that literal comprehension was highest (77.85 per cent) and inferential comprehension was lowest (60.60 per cent). These findings reveal a persistent surface-to-depth gradient in reading ability, with students demonstrating competence in basic text retrieval but significant difficulty in higher-order inferential and evaluative thinking. For pre-service teachers, this gap is not merely academic. It directly limits their capacity to foster critical literacy in future classrooms. The study contributes an empirically grounded, indicator-level literacy profile to the limited body of Indonesian PGSD research and calls for targeted, first-year instructional interventions to strengthen higher-order reading comprehension.